Carbon Emission Disclosure, Capital Expenditure, and Institutional Ownership on Company Value: A Literature Review - Aisyah, Siti; Evana, Einde; Metalia, Mega (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This literature review explores the impact of carbon emission disclosure on company value, synthesizing findings from eight recent peer-reviewed articles published between 2021 and 2023. The analysis reveals a consistent positive relationship between carbon emission disclosure and firm value, driven by increased investor confidence and enhanced market responses. Institutional investors play a crucial role in this dynamic, promoting sustainable practices and holding companies accountable for their environmental impact. Additionally, the review highlights the multifaceted relationship between capital expenditure and firm value, influenced by factors such as market competition and information asymmetry. Capital investments, particularly in sustainable practices, are shown to enhance transparency and corporate governance, further boosting firm valuation. The findings underscore the growing importance of environmental, social, and governance (ESG) criteria in investment decisions, suggesting that companies engaging in proactive carbon emission disclosure and sustainability investments are better positioned to attract responsible investors and achieve long-term market success. This comprehensive review provides valuable insights for policymakers, investors, and corporate leaders, emphasizing the strategic significance of carbon emission transparency and sustainable investments in fostering sustainable economic growth and improving company value.